2019
DOI: 10.1021/acs.inorgchem.9b02713
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Fe(II) Spin-State Equilibria via Eu(III) Luminescence in Molecular Complexes: Dream or Reality?

Abstract: The modulation of light emission by Fe(II) spin-crossover processes in multifunctional materials has recently attracted major interest for the indirect and non-invasive monitoring of magnetic information storage. In order to approach this goal at the molecular level, three segmental ligand strands L4-L6 were reacted with stoichiometric mixtures of divalent d-block cations (M(II) = Fe(II) or Zn(II)) and trivalent lanthanides (Ln(III) = La(III), Eu(III)) in acetonitrile to give C3-symmetrical dinuclear triplestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 80 publications
(83 reference statements)
1
39
0
Order By: Relevance
“…Benefiting from the huge amount of experimental data collected during the last decades for [Fe(N ∩ N)3] 2+ complexes, where N ∩ N is an α,α'-diimine chelate ligand possessing two N-heterocyclic donor atoms, it was shown that the connection of a six-membered heterocycle to a five-membered heterocycle in N ∩ N provides favorable ligand-field strengths around Fe II for promoting spin-state equilibria (Equation 5) with transition temperatures T1/2 = ∆HSCO/∆SSCO (i.e., the temperature at which ∆GSCO = 0 and xhs = xls = 0.5) within the 30-500 K range [14,15,33]. [35,36]. [35].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Benefiting from the huge amount of experimental data collected during the last decades for [Fe(N ∩ N)3] 2+ complexes, where N ∩ N is an α,α'-diimine chelate ligand possessing two N-heterocyclic donor atoms, it was shown that the connection of a six-membered heterocycle to a five-membered heterocycle in N ∩ N provides favorable ligand-field strengths around Fe II for promoting spin-state equilibria (Equation 5) with transition temperatures T1/2 = ∆HSCO/∆SSCO (i.e., the temperature at which ∆GSCO = 0 and xhs = xls = 0.5) within the 30-500 K range [14,15,33]. [35,36]. [35].…”
Section: Introductionmentioning
confidence: 99%
“…[35]. Whereas the connection of methyl groups adjacent to the donor nitrogen atom in the bound 6-methyl-pyridine groups in [Fe(L4) 3 ] 2+ produces such large inter-strand interactions that the contraction accompanying the high-spin to low-spin transition cannot be envisioned [41], the situation with the remote 3-methyl substituted pyridine units in [Fe(L3) 3 ] 2+ is less clear and a sophisticated triple-stranded heterometallic LaFe helicate containing the facial [Fe(L3) 3 ] 2+ chromophore has been shown to display partial SCO behavior at low temperature (T 1/2~5 0 K) [36]. Taking into account that (i) the replacement of a pyridine with a pyrazine ring in going from [Fe L1 [36].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations